Revolutionizing Age Determination: Theoretical Insights into Radiocarbon (14C) Dating - Baral, Dipak; Budhathoki, Sujan; Bhattarai, Ajaya; Chaudhary, Narendra Kumar (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
Radiocarbon dating is a scientific method for determining the age of ancient organic materials, specimens, and artifacts based on the decay of 14C isotopes. This study outlines the mode of formation and assimilation of 14C isotopes in the atmosphere. A traditional carbon-14 dating method estimates sample age by measuring β-ray decay, however, this new technique uses an incredibly sensitive mass spectrometer to count individual carbon-14 atoms in a sample directly. This approach offers several advantages. It eliminates issues related to the cosmic ray background and allows for shorter counting times on much smaller samples, leading to more precise age determinations. Moreover, a wide range of archaeological materials can be dated using milligram-sized samples. Currently, research is underway to develop a specialized machine for counting C-14 atoms, and radiocarbon dating cannot provide exact dates for archaeological or environmental studies on its own. Instead, it needs to use a calibration curve to adjust for changes in atmospheric carbon levels. Any model that proposes the validity of C-14 dating must acknowledge its objectivity and reproducibility. The fundamental principles, methods, and methodology of accelerator mass spectrometry (AMS), and the history, evolution, and revolution in radiocarbon dating techniques are presented in this review.